Analisis Gaya Kepemimpinan dan Motivasi Kerja terhadap Kinerja Pegawai Perguruan Tinggi di Kabupaten Maros - Hanafi, Muh. Alam Nasyrah; Waworuntu, Ahmad Yusdarwin (Patria Artha University, 2017)
ABSTRACTA good organization is an organization that seeks to improve the capabilities of its human resources, as it is a key factor in improving employee performance. Employee performance is the result or performance of employees who assessed in terms of quality and quantity based on work standards determined by the organization. Leadership style has a significant influence on employee performance. The effect of work motivation on performance shows the same result that the relationship between motivation and employee performance shows a positive and significant relationship. The purpose of this study is to analyze the influence of leadership style on employee performance, and analyze the effect of work motivation on employee performance. This research uses primary and secondary data. The population of this study were all employees in the three colleges of Maros Regency. Data collection was done by observation and interview. In the determination of respondents done by a method intentionally where all members of the population sampled in the study. Data processing is done by using tabulation and percentage. The analysis used is the analysis of quantitative data and single regression. The results showed that: (1) leadership style had real and positive effect on employee performance, whereas relationship (correlation) leadership style with employee performance categorized low relation. (2) Work motivation has real and positive effect on employee performance, while the correlation of work motivation with employee performance is categorized low relation.